After Christianity - Vattimo, Gianni (New York Columbia University Press, 2002)
What has been the fate of Christianity since Nietzsche's famous announcement of the ""death of God""? What is the possibility of religion, specifically Christianity, thriving in our postmodern era? In this provocative new book, Gianni Vattimo, leading Ita
Keywords: Christianity. RELIGION -- Christianity -- General. RELIGION -- Christian Theology -- Systematic